Zur Kollokationsbewusstheit und zum Kollokationsbewusstsein bei thailändischen DaF-Studierenden im Vergleich verschiedener Jahrgänge : (Eine empirische Studie) - Teroerde, Rasmus (Manutsat Paritat: Journal of Humanities, 2025)
Research in the field of German as a foreign language has long been concerned with the linguistic phenomenon of collocations, which has gained new relevance particularly in the context of the so-called "Wortschatzwende" or “vocabulary turn”. There has been considerable focus on the concept of collocational competence, defined as the ability to reflexively and productively master collocations. However, less attention has been given to what underpins collocational competence. From the author’s perspective, the concepts of "collocational awareness" and "collocational consciousness" play a central role in developing collocational competence among learners. Therefore, this paper demonstrates, through a study involving participants from various undergraduate cohorts, what levels of collocational awareness and consciousness the participants possess, and whether both aspects are enhanced in a comparative analysis of the cohorts, even within the context of an implicit approach to the subject in teaching and therefore without explicit instruction. In the course of the present article, the concept of collocation will first be redefined, and the current state of research will be presented, upon which the study is based. This study includes a questionnaire to assess collocational awareness and a test to evaluate collocational consciousness. Following the study, key reasons for making collocations explicit in DaF (German as a foreign language) instruction will be presented, along with strategies for enhancing collocational awareness and consciousness. Finally, a conclusion and a perspective on the future of teaching collocations in DaF will be formulated based on the results of the study.